Plant root exudates: Advances in belowground signaling networks, resilience, and ecosystem functioning for sustainable agriculture - Ajay M. Sorty; Enoch N. Kudjordjie; Kamlesh K. Meena; Mogens Nicolaisen; Peter Stougaard (Plant Stress)
Root exudates (REs), the secretory carbonaceous metabolites from plant roots play a crucial role in belowground ecosystem dynamics in response to biogeochemical shifts. An intricate pool of primary and secondary metabolites including organic acids, amino acids, peptides, carbohydrates, phenolics, and hormones make REs key influencers of belowground chemical ecology. Their profiles are vulnerable to abiotic and biotic stress, thus potentially hindering beneficial interactions due to stress-induced dysbiosis.As sensitive molecular markers of plant influence on belowground ecosystem functions, REs have significant implications for agro-industrial productivity. Typically, REs mediate critical biotic and abiotic processes, shaping interactions with multiple life forms including soil microbes, insects, and neighboring plants. Understanding these multi-kingdom crosstalks can enhance cropping practices and strengthen resilient agricultural systems under changing climate. This review updates the current knowledge on REs, covering their chemical and ecological roles, and systems-level functions across environmental contexts. Further, strategic applications of RE-based interactions in agroecology and soil health, potential benefits and challenges are also discussed. The emerging science of REs offers new possibilities for chemical ecology-driven innovations in sustainable agriculture and ecosystem management.